1987
DOI: 10.1038/328166a0
|View full text |Cite
|
Sign up to set email alerts
|

The mapping of a cDNA from the human X-linked Duchenne muscular dystrophy gene to the mouse X chromosome

Abstract: The recent discovery of sequences at the site of the Duchenne muscular dystrophy (DMD) gene in humans has opened up the possibility of a detailed molecular analysis of the genes in humans and in related mammalian species. Until relatively recently, there was no obvious mouse model of this genetic disease for the development of therapeutic strategies. The identification of a mouse X-linked mutant showing muscular dystrophy, mdx, has provided a candidate mouse genetic homologue to the DMD locus; the relatively m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…An interspecific Mus domesticus/Mus spretus cross segregating for the coattexture mutations Hq, Ta, and Li (13) was used to generate backcross progeny for the genetic analysis of DXSmh141 and other microclones and has been described in detail (14,15). High molecular weight DNA was prepared from mouse tails (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interspecific Mus domesticus/Mus spretus cross segregating for the coattexture mutations Hq, Ta, and Li (13) was used to generate backcross progeny for the genetic analysis of DXSmh141 and other microclones and has been described in detail (14,15). High molecular weight DNA was prepared from mouse tails (14).…”
Section: Methodsmentioning
confidence: 99%
“…Progeny DNAs from the backcross were restriction digested and Southern blotted onto Hybond-N membranes (Amersham) by standard methods. Filters were hybridized as described (15) and washed with 2x NaCl/Cit/0.1% NaDodSO4 at 650C and autoradiographed overnight at -70'C with intensification (lx NaCl/Cit = 0.15 M NaCI/0.015 M sodium citrate). Clone versus clone hybridizations were washed extensively in 0.1x NaCI/Cit/0.1% NaDodSO4 at 650C and autoradiographed at room temperature for <1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…These strategies, alone or in combination, have been utilised in inbred mice to identify genetic mechanisms of a number of diseases. These include models of Huntingtons disease [6,7], Duchenne muscular dystrophy [8], amyotrophic lateral sclerosis [9], insulindependent diabetes mellitus [10], Alzheimer9s disease [11], von Willebrand disease [12], chronic granulomatous disease [13], and Niemann-Pick C1 disease [14]. The considerable resources and energy applied to mapping of the mouse genome as an integral component of the Human Genome Project underlie the importance of this animal model for human diseases [15].…”
Section: Research Strategies Employed To Identify Candidate Genesmentioning
confidence: 99%
“…Some mapping studies have shown that the mdx mutation is in a region of the mouse X chromosome close to the mouse homologue of DMD (Brockdorff et al, 1987a;Heilig et al, 1987). However, it has also been mapped close to a cluster of genes which, on the human chromosome, includes the Emery -Dreifus muscular dystrophy (EDMD) locus Chamberlain et al, 1987), making it uncertain to which, if either, of these two loci on the human X chromosome mdx is equivalent.…”
mentioning
confidence: 99%